Developing Worksheets Through Creative Problem Solving (CPS) Model to Improve Students' Creative Thinking for the Class V of SD Tunas Bangsa Makassar - Jusmawati Jusmawati; Satriawati Satriawati; Irman Rahim; Abdul Rahman; Nurdin Arsyad (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
This research aims to develop worksheets through Creative Problem Solving (CPS) model to improve students' creative thinking. The implementation of the research conducted by Research & Development (R & D), with a model of Four-D development. This model consists of 4 stages of development: Define, Design, Develop and Disseminate, with the development of learning mathematics of worksheets for the material fractions through Creative Problem Solving (CPS) model to improve creative thinking the fifth-grade students of SD Tunas Bangsa Makassar. The instrument used in this research was the sheet validity test, sheet test the practicalities, and the post-test (students thinking creatively). Based on the validity test results, worksheets through the model of creative problem solving (CPS) with an average value of 4,01 and valid category. While the test results in the practicalities when the trial was limited worksheets with model creative problem solving (CPS) belongs to the category was very practical, with the percentage of 82,43%. Based on the post-test results, students' creative thinking was the category of creative with a percentage of 81,68%. Finally, it can be concluded that worksheets through a model of creative problem solving (CPS) to improve students' creative thinking that developed were valid, practical, and useful. So it can be applied in class V of mathematics subject.